2022
DOI: 10.2219/rtriqr.63.4_238
|View full text |Cite
|
Sign up to set email alerts
|

<b>Anomaly Detection for Railway Vehicle Equipment Using Condition Monitoring Data</b>

Abstract: In recent years, some railway vehicles have been equipped with condition monitoring devices, which constantly record the operating condition of railway vehicle equipment. For more effective use of condition monitoring devices, we propose an anomaly detection method for railway vehicle equipment using Long Short-Term Memory (LSTM), which is a deep learning method suitable for learning time-series data. In this paper, we apply the proposed method to data on engines and air-conditioning units recorded on vehicles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…One example of these initiatives includes the proposal of a method for automatically judging anomalies from vehicle condition monitoring data using deep learning techniques. Results of attempts to apply this to engine stop events and engine overheating events of diesel railcars showed that it was possible to determine the anomaly before the event occurred [17].…”
Section: Anomaly Detection Methodsmentioning
confidence: 99%
“…One example of these initiatives includes the proposal of a method for automatically judging anomalies from vehicle condition monitoring data using deep learning techniques. Results of attempts to apply this to engine stop events and engine overheating events of diesel railcars showed that it was possible to determine the anomaly before the event occurred [17].…”
Section: Anomaly Detection Methodsmentioning
confidence: 99%